Оpen government in Russia (Journal of actual problems of jurisprudence, 2019)
The article covers issues of formation and functioning of the system of open government in Russia, as a new governancemechanism, which is based on broad public participation in state activities.Key words: open government, management mechanism, Russian public initiative.